2014
DOI: 10.1111/1477-8947.12042
|View full text |Cite
|
Sign up to set email alerts
|

Extending theEU RenewableEnergyDirective sustainability criteria to solid bioenergy from forests

Abstract: Solid bioenergy from forests plays -and is expected to continue to play -a key role to fulfil the renewable energy targets at the European Union level. When the Renewable Energy Directive was enacted, sustainability criteria were incorporated solely for biofuels and bioliquids. Sustainability criteria for solid bioenergy are also needed in order to prevent wood and primary forest residues from posing additional environmental risks to ecosystems. Acknowledging this, the European Commission has been working on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…-Therefore, soils with low fertility and smaller nutrient pools are more subject to suffer from the removal of residues and nutrients (Fritsche et al, 2014). -Stumps contain a small fraction of macronutrients, but coarse roots are responsible for significant inputs of nitrogen and potassium to the soil (Moffat et al, 2011).…”
Section: Impact Category Potential Risks/benefits Mitigation Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…-Therefore, soils with low fertility and smaller nutrient pools are more subject to suffer from the removal of residues and nutrients (Fritsche et al, 2014). -Stumps contain a small fraction of macronutrients, but coarse roots are responsible for significant inputs of nitrogen and potassium to the soil (Moffat et al, 2011).…”
Section: Impact Category Potential Risks/benefits Mitigation Measuresmentioning
confidence: 99%
“…Nitrogen is almost completely lost during combustion, so it is not present in ashes and will need to be supplied via synthetic or organic fertilisers. Experimental data have shown increased growth rates in fertilised forests, but guidelines in some countries still advise against synthetic forest fertilisation (Fritsche et al, 2014;Stupak et al, 2007). Avoid extraction on rocky, dry and poor soils (Lamers et al, 2013;Wall, 2012) Soil health and productivity ¼ Many studies have shown results that are not statistically different when comparing trees grown on sites where residues are either collected or left on floor.…”
Section: Impact Category Potential Risks/benefits Mitigation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding intensification, on the other hand, sensitive issues are, among others, those connected to the intensive utilization of meadows [45] or the use of wood biomass for energy supplies [46][47][48]. These days, in fact, there is increasing interest in the use of wood as a source of energy in order to reach the European objective regarding renewable energy sources [49,50].…”
Section: A Problem Of Governancementioning
confidence: 99%
“…Voluntary forest biomass harvesting guidelines Guidance on reducing impacts of different woody biomass cultivation and harvesting systems, e.g., in Finland, France, Germany, several Canadian and US (see e.g., [30]). …”
Section: Voluntary Forest Certification Schemesmentioning
confidence: 99%